Substrate with film

By designing a film-containing glass substrate with both thermal and light barrier functions, the problems of low productivity and high cost of laminated glass in the prior art are solved, and the efficient manufacturing of a variety of laminated glass and the performance of panoramic roof are achieved. .

CN119409426AInactive Publication Date: 2025-02-11AGC INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311360532.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-12-28
Filing Date
2022-05-25
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to improve productivity when manufacturing laminated glass suitable for panoramic roofs, and a variety of intermediate films and plate glasses are required, resulting in increased costs.

Method used

By designing a film-containing glass substrate with both thermal and light barrier functions, it can be combined with a general intermediate film to reduce the number of varieties of glass substrate and intermediate film.

Benefits of technology

It achieves productivity improvement and cost reduction when manufacturing a variety of laminated glasses, while meeting the transmittance and emissivity requirements of the panoramic roof.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409426A_ABST
    Figure CN119409426A_ABST
Patent Text Reader

Abstract

The invention relates to a substrate with a film. Provided is a method for improving productivity in the production of laminated glass. This substrate with a film has a glass substrate having a plate thickness of 5 mm or less and a first surface and a second surface which are opposite to each other, and a film disposed on the glass substrate, the film being provided on the first surface of the glass substrate, the film being provided on the second surface of the glass substrate, the film being provided on the first surface of the glass substrate, and the film being provided on the second surface of the glass substrate. The substrate with the film has a transmittance of less than 30% based on a standard A light source and an emissivity of less than 0.25 of the side surface of the film.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application date of May 25, 2022 and application number 202280010183.8. Technical Field

[0002] The present invention relates to a substrate with a film, and more particularly, to a substrate with a film suitable for laminated glass. Background Art

[0003] Substrates with films, such as glass substrates with thin films and films with thin films, are widely used in various fields as materials satisfying various required properties by laminating functional films on glass or films as main materials.

[0004] For example, in window glass used in vehicles and buildings, low-emissivity glass (Low-E glass) having heat-blocking and heat-shielding properties is used in view of the increasing awareness of energy conservation in recent years. Low-emissivity glass is formed by laminating one or more functional layers containing metal oxides on a glass substrate, and has, for example, a heat ray reflecting layer, a heat ray absorbing layer, a visible light reflecting layer, a visible light absorbing layer, an optical adjustment layer, etc. as functional layers.

[0005] As such low-emissivity glass, for example, Patent Document 1 describes a low-emissivity glass, which includes at least an antimony-containing / tin oxide-based film containing antimony and a fluorine-containing / tin oxide-based film containing fluorine as metal oxide-based films on the surface of a glass substrate. In addition, Patent Document 2 describes a coated glass product, which includes (a) a glass substrate, (b) an antimony-doped tin oxide coating attached to the above-mentioned glass substrate, and (c) a fluorine-doped tin oxide coating attached to the above-mentioned antimony-doped tin oxide coating, and the thickness of the coating is selected so that the coated glass product has a difference between the visible light transmittance (reference light source C) and the total solar energy transmittance (under the condition of air quality 1.5) on a transparent glass substrate with a nominal thickness of 3 mm, providing a selectivity of 13 or more.

[0006] In addition, when laminated glass is broken by external impact, the amount of scattered glass fragments is small and the safety is excellent, so it is widely used in window glass of vehicles, aircraft, buildings, etc. As laminated glass, there can be cited a laminated glass obtained by sandwiching an interlayer between at least a pair of plate glasses and integrating them, and the desired effect can be obtained by utilizing the functions of each constituent member.

[0007] As such laminated glass, for example, Patent Document 3 describes a sunshade having a heat ray shielding function, in which the visible light transmittance of the sunshade is reduced and the solar transmittance and visible light transmittance satisfy a specific relationship, and describes a laminated glass in which the sunshade is sandwiched between two sheets of plate glass as an intermediate film. In addition, Patent Document 4 proposes a panoramic vehicle roof laminate having at least one plastic adhesive layer between a first glass layer and a second glass layer, the visible light transmittance of the plastic adhesive layer being less than 50%.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2001-199744

[0011] Patent Document 2: Japanese Patent Application No. 2003-535004

[0012] Patent Document 3: Japanese Patent Application Publication No. 2008-44609

[0013] Patent Document 4: International Publication No. 2019 / 008471 Summary of the invention

[0014] Problems to be solved by the invention

[0015] For example, a panoramic roof of a vehicle is required to have heat shielding properties, heat barrier properties, and a high-end color. In response to such requirements, at least one plate glass in the laminated glass has been made of low-emissivity glass and has an intermediate film that reduces the visible light transmittance, thereby achieving both the desired transmittance and emissivity.

[0016] In recent years, with the increasing demand for panoramic roofs, the demand for transmittance and emissivity has also become diversified. Manufacturers need to produce a variety of products. As the number of varieties increases, a variety of interlayer films and plate glass must also be prepared, which makes it difficult to improve productivity.

[0017] In addition, the transmittance suitable for the panoramic roof is between 3% and 8%. When the components facing the glass of the panoramic roof are unified into inexpensive components, a transparent intermediate film is preferably used as the intermediate film, and one of the glasses is preferably a colored glass or a glass with an Ag sputtering film. However, as a glass substrate with a film matching the intermediate film and one of the glasses, there has been no substrate that can provide a laminated glass suitable for the panoramic roof by combining these intermediate films and glasses.

[0018] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a means for improving productivity when manufacturing laminated glass.

[0019] Means used to solve problems

[0020] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by providing a glass substrate with a film with both a heat shielding function and a light shielding function, thereby completing the present invention.

[0021] The present invention includes the following aspects.

[0022] (1) A substrate with a film, the substrate with a film comprising a glass substrate and a film arranged on the glass substrate, wherein the glass substrate has a thickness of 5 mm or less, the glass substrate has a first surface and a second surface opposite to each other, the film is arranged on the first surface of the glass substrate, the transmittance of the substrate with the film based on a standard A light source is less than 30%, and the emissivity of the side surface of the film is less than 0.25.

[0023] (2) A vehicle window glass comprising the substrate with a film as described in (1) above.

[0024] (3) A laminated glass comprising the substrate with a film as described in (1), an intermediate film, and an outer glass plate in this order.

[0025] (4) A panoramic roof comprising the laminated glass described in (3) above.

[0026] Effects of the Invention

[0027] The substrate with a film of the present invention has a heat-blocking function and a light-blocking function. Therefore, when manufacturing laminated glass, it is not necessary to separately manufacture both the glass substrate and the intermediate film for each type. Instead, the substrate with a film can be manufactured by changing the heat-blocking property and transmittance of the glass substrate, and a common intermediate film can be used. Since the intermediate film can be made common, productivity can be improved and costs can be reduced even when manufacturing multiple types of laminated glass.

[0028] In addition, the transmittance of the panoramic roof facing the car based on the standard A light source (hereinafter also referred to as the A light source transmittance) is usually between 3% and 8%. In the case of making laminated glass with a structure in which the A light source transmittance of the substrate with a film of the present invention is adjusted from 3% to 13% and the substrate with a film, a transparent intermediate film and a colored glass are stacked in this order, the A light source transmittance can be 3% to 8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a cross-sectional view of a substrate with a film for explaining the structure of one embodiment of the substrate with a film of the present invention.

[0030] Figure 2This is a cross-sectional view of a substrate with a film for explaining the structure of another embodiment of the substrate with a film of the present invention.

[0031] Figure 3 This is a flow chart schematically showing an example of the method for producing a film-attached substrate of the present invention. DETAILED DESCRIPTION

[0032] Hereinafter, the present invention will be described, but the present invention is not limited to the examples in the following description.

[0033] It should be noted that, in this specification, “mass” and “weight” have the same meaning.

[0034] The substrate with a film of the present invention comprises a glass substrate and a film disposed on the glass substrate. The film imparts the desired function to the glass substrate with a film. The substrate with a film of the present invention is a substrate having a transmittance of less than 30% based on a standard A light source and an emissivity of less than 0.25 on the film side surface. The film may include one layer or two or more layers.

[0035] exist Figure 1 One embodiment of the substrate with a film of the present invention is shown in FIG. Figure 1 The substrate 10 with a film shown has a glass substrate 1 and a film 2 disposed on the glass substrate 1. The glass substrate has a first surface 1a and a second surface 1b opposite to each other, and the film 2 is disposed on the first surface 1a of the glass substrate 1. In the present embodiment, the film 2 is a laminated film having a heat ray absorbing layer 3 and an infrared reflecting layer 5 from the side close to the glass substrate 1.

[0036] Each layer is described below.

[0037] (Glass Substrate)

[0038] The glass substrate 1 is the framework of the base material 10 with a film and has self-supporting properties.

[0039] Examples of the glass constituting the glass substrate include soda-lime silicate glass, aluminosilicate glass, borate glass, lithium aluminosilicate glass, quartz glass, borosilicate glass, and alkali-free glass.

[0040] The glass substrate can be transparent, semi-transparent or opaque depending on the use and purpose of the substrate with the film. In addition, the glass substrate can be colorless or colored.

[0041] The shape of the glass substrate is not particularly limited, and may be a plate, a film, a sheet, etc., and may be any shape depending on the intended use. For example, in order to use it in a vehicle member or a building member, a plate shape is preferred.

[0042] The thickness of the glass substrate is 5 mm or less. When the thickness of the glass substrate is 5 mm or less, it is a thickness suitable for vehicle mounting.

[0043] The thickness of the glass substrate is preferably 4.5 mm or less, more preferably 4.3 mm or less, and further preferably 4.1 mm or less. The thickness of the glass substrate is preferably 1 mm or more, more preferably 1.3 mm or more, and further preferably 1.6 mm or more.

[0044] The size (area) of the glass substrate is not particularly limited and can be appropriately adjusted according to the application and purpose of use of the film-attached substrate.

[0045] For example, when the substrate with a film is used in a vehicle, the area of ​​the main surface of the glass substrate is preferably 0.5 m 2 ~5m 2 When the substrate with the film is used in a building, the area of ​​the main surface of the glass substrate is preferably 0.5 m 2 ~10m 2 .

[0046] (membrane)

[0047] exist Figure 1 In the illustrated embodiment, the film laminated on the glass substrate has the heat ray absorbing layer 3 and the infrared reflecting layer 5 from the side close to the glass substrate 1 .

[0048] <Heat ray absorbing layer>

[0049] The heat ray absorbing layer 3 is a layer that reflects solar radiation heat and imparts heat shielding properties to the film-attached substrate, and has crystallinity.

[0050] As materials forming the heat ray absorbing layer, for example, metal oxides such as tin oxide, indium oxide, zinc oxide, titanium oxide, niobium oxide, and tantalum oxide can be cited. In addition, the metal oxide forming the heat ray absorbing layer can be a doped metal oxide doped with other elements (impurity elements). By forming the heat ray absorbing layer with a doped metal oxide, the desired function can be imparted to the heat ray absorbing layer.

[0051] Examples of the impurity element doped into the doped metal oxide include antimony, fluorine, tin, potassium, aluminum, tantalum, niobium, nitrogen, boron, and indium.

[0052] When a doped metal oxide is used in the formation of the heat ray absorbing layer, the concentration of the doped impurity element is preferably 30 mol% or less. When the concentration of the impurity element is 30 mol% or less, the crystal structure before doping can be maintained. The concentration of the impurity element is preferably 30 mol% or less, more preferably 25 mol% or less, and further preferably 20 mol% or less. In addition, the concentration of the impurity element is preferably 0.1 mol% or more. From the viewpoint of easily reducing the transmittance of the substrate with the film to a specified value, the concentration of the impurity element is more preferably 1 mol% or more, more preferably 2 mol% or more, particularly preferably 4 mol% or more, and most preferably 6 mol% or more.

[0053] In the present invention, the heat ray absorbing layer preferably has tin oxide (ATO, in SnO 2 The antimony-doped tin oxide film provides excellent heat shielding properties to the substrate with the film by reducing the amount of heat transferred to the inside of the substrate.

[0054] It should be noted that the antimony concentration contained in the heat ray absorbing layer is preferably 5 mol% to 20 mol%. When the antimony concentration in the heat ray absorbing layer is 5 mol% or more, heat shielding properties can be exhibited and transmittance can be reduced. When the antimony concentration is 20 mol% or less, the crystal structure before doping can be maintained. The antimony concentration contained in the heat ray absorbing layer is more preferably 6 mol% or more, further preferably 7 mol% or more, particularly preferably 8 mol% or more, and more preferably 19 mol% or less, further preferably 18 mol% or less, and particularly preferably 15 mol% or less.

[0055] It should be noted that the composition of the heat ray absorbing layer and the concentration of the doped impurity element can be identified by X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS).

[0056] For example, the concentration of antimony (Sb) is analyzed in depth by X-ray photoelectron spectroscopy (XPS), and the intensity ratio of Sb to Sn is used to investigate. The concentration of fluorine (F) is analyzed in depth by secondary ion mass spectrometry (SIMS), and the intensity ratio of F to Sn is used to investigate. It should be noted that SIMS requires the measurement of SnO with a known concentration of fluorine added. 2 , and find the coefficient for converting the F / Sn intensity ratio to concentration.

[0057] The heat ray absorbing layer may consist of a single film, or may consist of two or more films having different materials, metal contents, and the like.

[0058] In the present invention, the thickness of the heat ray absorbing layer is preferably 300nm to 700nm. When the thickness of the heat ray absorbing layer is more than 300nm, sufficient heat shielding properties are given to the substrate with the film, and the transmittance of the substrate with the film is easily adjusted to a specified value. In addition, the crystal grains in the heat ray absorbing layer can be grown to a certain extent, so when the infrared reflecting layer is formed, it is easy to increase the crystal grain size in the infrared reflecting layer. When the thickness of the heat ray absorbing layer is less than 1000nm, it is easy to keep the film surface flat.

[0059] The thickness of the heat ray absorbing layer is more preferably 350 nm or more, further preferably 400 nm or more, particularly preferably 450 nm or more, and is more preferably 900 nm or less, further preferably 800 nm or less, particularly preferably 700 nm or less.

[0060] The thickness of the heat ray absorbing layer can be measured by, for example, analysis in the depth direction of X-ray photoelectron spectroscopy.

[0061] It should be noted that since the heat ray absorbing layer is formed of crystal grains of metal oxide, it has a concavo-convex shape on the surface opposite to the glass substrate side. Therefore, the "thickness" of the heat ray absorbing layer varies depending on the location, but in the present invention, it represents the average thickness of the heat ray absorbing layer in the measurement area.

[0062] The size of the crystal grains in the heat ray absorbing layer is preferably 30 nm to 1500 nm. When the crystal grain size is 30 nm or more, the crystal grain shape of the infrared reflecting layer formed on the heat ray absorbing layer can be sufficiently enlarged, and the emissivity can be reduced.

[0063] The grain size is preferably greater than 30 nm, more preferably greater than 50 nm, and further preferably greater than 80 nm. In addition, the larger the grain shape, the better, so there is no particular upper limit, but it is generally preferably less than 1500 nm, more preferably less than 1200 nm, and further preferably less than 1000 nm.

[0064] The size of the crystal grains can be measured by observing a cross section of a substrate with a film cut in the thickness direction using a scanning electron microscope (SEM).

[0065] <Infrared reflection layer>

[0066] The infrared reflecting layer 5 is a layer that reflects infrared rays and imparts heat-shielding properties to the film-attached substrate, and has crystallinity.

[0067] Examples of the material forming the infrared reflection layer include doped metal oxides obtained by doping at least one metal oxide selected from the group consisting of tin oxide, indium oxide, zinc oxide, titanium oxide, tantalum oxide, and niobium oxide with other elements (impurity elements).

[0068] Examples of the impurity element to be doped include fluorine, antimony, tin, potassium, aluminum, tantalum, niobium, nitrogen, boron, and indium.

[0069] Specific examples of doped metal oxides include fluorine-doped tin oxide (FTO, in SnO 2 Metal oxides obtained by adding F to SnO), antimony-doped tin oxide (ATO, in SnO 2 Metal oxides obtained by adding Sb to indium oxide (ITO, indium oxide doped with tin) 2 O 3 The following are some of the metal oxides that are obtained by adding Sn to ZnO: zinc oxide doped with gallium (GZO, a metal oxide obtained by adding Ga to ZnO); zinc oxide doped with aluminum (AZO, a metal oxide obtained by adding Al to ZnO); tantalum-doped tin oxide (tin oxide in SnO); 2 Metal oxides obtained by adding Ta to niobium), tin oxide doped with niobium (in SnO 2 metal oxides obtained by adding Nb to tantalum-doped titanium oxide (in TiO 2 metal oxides obtained by adding Ta to niobium), titanium oxide doped with niobium (in TiO 2 Metal oxides obtained by adding Nb to ), aluminum-doped tin oxide (in SnO 2 Metal oxides obtained by adding Al to ), fluorine-doped titanium oxide (in TiO 2 metal oxides obtained by adding F to TiO 2 Metal oxides obtained by adding N to

[0070] Among them, the infrared reflecting layer preferably has a film containing a doped metal oxide, which is obtained by doping other elements into at least one metal oxide selected from the group consisting of tin oxide, indium oxide and zinc oxide, and the other elements are preferably at least one selected from the group consisting of fluorine, antimony, tin, gallium and aluminum.

[0071] Specifically, the infrared reflective layer more preferably has a film of at least one doped metal oxide selected from the group consisting of fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO) and aluminum-doped zinc oxide (AZO), and from the viewpoint of obtaining higher thermal barrier properties, it is further preferred to have a fluorine-doped tin oxide (FTO) film.

[0072] The infrared reflection layer may include a single film, or may include two or more films having different materials, element contents, and the like.

[0073] The content of the impurity element contained in the infrared reflection layer is preferably in the range of 0.01 mol% to 20 mol%. When the concentration of the impurity element contained in the infrared reflection layer is 0.01 mol% or more, a heat-shielding effect can be exhibited, and the transmittance of the substrate with the film can be easily adjusted to a predetermined value. When the concentration of the impurity element contained in the infrared reflection layer is 20 mol% or less, good crystallinity can be maintained.

[0074] The concentration of the impurity elements contained in the infrared reflecting layer is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, further preferably 0.5 mol% or more. The concentration of the impurity elements contained in the infrared reflecting layer is more preferably 10 mol% or less, further preferably 8 mol% or less, particularly preferably 5 mol% or less.

[0075] It should be noted that, when a plurality of impurity elements are contained in the infrared reflecting layer, the concentration of the impurity elements is the total amount thereof.

[0076] It should be noted that, as described above, the composition of the infrared reflective layer and the concentration of the impurity elements can be identified by X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS).

[0077] In the present invention, the thickness of the infrared reflection layer is preferably 100 nm to 400 nm. When the thickness of the infrared reflection layer is 100 nm or more, the heat barrier performance of the substrate with the film is improved, and it is easy to adjust the transmittance of the substrate with the film to a specified value. When the thickness of the infrared reflection layer is 400 nm or less, the surface can be flattened.

[0078] The thickness of the infrared reflection layer is more preferably 120 nm or more, further preferably 130 nm or more, particularly preferably 150 nm or more, and the thickness of the infrared reflection layer is more preferably 380 nm or less, further preferably 350 nm or less.

[0079] The thickness of the infrared reflection layer can be measured by depth analysis of X-ray photoelectron spectroscopy or the like.

[0080] When the infrared reflective layer is composed of a plurality of layers of different materials, the “thickness” of the infrared reflective layer is represented by the total of the thicknesses of the respective layers.

[0081] It should be noted that the infrared reflective layer is formed of crystal grains of metal oxide, and the surface of the heat ray absorbing layer stacked with the infrared reflective layer is concavoconvex, so the surface of the layer (i.e., the surface on the side of the heat ray absorbing layer and the surface on the opposite side of the heat ray absorbing layer) has a concavoconvex shape. Therefore, the "thickness" of the infrared reflective layer varies depending on the location, but in the present invention, it means the average thickness of the infrared reflective layer in the measurement area.

[0082] The crystal grain size in the infrared reflective layer is preferably 30 nm or more. When the crystal grain size is 30 nm or more, the grain boundary scattering of electrons is reduced, the conductivity is improved, and the emissivity is reduced, so that the desired effect of the present invention is easily obtained.

[0083] The grain size is preferably greater than 30 nm, more preferably greater than 50 nm, and further preferably greater than 80 nm. In addition, the larger the grain shape, the better, so there is no particular upper limit, but it is generally preferably less than 1000 nm, more preferably less than 800 nm, and further preferably less than 500 nm.

[0084] In addition, the measurement of the size of a crystal grain can be measured by cross-sectional observation using a scanning electron microscope (SEM) in the same manner as described above.

[0085] The infrared reflective layer preferably has a surface arithmetic mean roughness Ra of 30 nm or less, and more preferably 25 nm or less.

[0086] It should be noted that the heat ray absorbing layer and the infrared reflecting layer are preferably formed by containing the same type of metal oxide. When the metal oxide contained in the heat ray absorbing layer and the metal oxide contained in the infrared reflecting layer are of the same type, the growth of the crystal grains will not be interrupted when the infrared reflecting layer is formed, and the crystal grains in the infrared reflecting layer can be grown larger. For example, when the metal oxide constituting the heat ray absorbing layer is tin oxide, the infrared reflecting layer is preferably a doped tin oxide film.

[0087] The substrate with film of the present invention preferably has a heat ray absorbing layer comprising an antimony-doped tin oxide (ATO) film, and an infrared reflective layer comprising a fluorine-doped tin oxide (FTO) film. In this configuration, the fluorine concentration contained in the infrared reflective layer is preferably 0.01 mol% to 10 mol%. When the fluorine concentration contained in the infrared reflective layer is 0.01 mol% or more, a sufficient heat barrier effect can be exhibited, and when the fluorine concentration contained in the infrared reflective layer is 10 mol% or less, the concentration of inactive fluorine can be suppressed, and impurity scattering becomes small, so that mobility can be improved.

[0088] The concentration of fluorine contained in the infrared reflecting layer is more preferably 0.05 mol % or more, and further preferably 0.1 mol % or more. The concentration of fluorine contained in the infrared reflecting layer is more preferably 5 mol % or less, and further preferably 3 mol % or less.

[0089] In the present invention, the total thickness of the infrared reflection layer and the heat ray absorption layer is preferably 500nm to 1500nm. When the total thickness of each layer is more than 500nm, the crystal grains in the infrared reflection layer can be fully grown, so the emissivity can be improved, and the transmittance can be easily adjusted to a specified range. When the total thickness of each layer is less than 1500nm, the thickness of the substrate with the film will not become too thick.

[0090] The total thickness of the infrared reflecting layer and the heat ray absorbing layer is more preferably 550 nm or more, further preferably 600 nm or more, particularly preferably 650 nm or more. In addition, the total thickness of the infrared reflecting layer and the heat ray absorbing layer is more preferably 1100 nm or less, further preferably 900 nm or less.

[0091] <Optical adjustment layer>

[0092] like Figure 2 As shown, the film 2 in the film-bearing substrate of the present invention may further include an optical adjustment layer 7. When the film-bearing substrate 20 includes the optical adjustment layer 7, the optical adjustment layer 7 is preferably disposed between the glass substrate 1 and the heat ray absorbing layer 3.

[0093] Examples of materials constituting the optical adjustment layer include silicon oxycarbide (SiOC), silicon oxide (SiO 2 ), titanium oxide (TiO 2 ), tin oxide (SnO 2 ), silicon oxynitride (SiON), etc. The optical adjustment layer may include one layer or two or more layers. In addition, it may be a mixture of any two or more of the above materials.

[0094] Specifically, as the optical adjustment layer, there can be mentioned SiOC film, SiOC film and SiO 2 Sequential stacking of SiOC / SiO films 2 Laminated film, TiO 2 Film and SiO 2 Sequential stacking of TiO films 2 / SiO 2 Laminated film, SnO from the glass substrate side 2 Film and SiO 2 Sequential stacking of SnO films 2 / SiO 2 Laminated films, etc.

[0095] Among them, from the viewpoint of alkali metal barrier properties, the optical adjustment layer preferably contains silicon, and more preferably has a film selected from the group consisting of SiOC film, SiOC / SiO 2 Laminated film, TiO 2 / SiO 2 Laminated film and SnO 2 / SiO 2 It is further preferred that at least one film in the group consisting of the stacked films includes a SiOC film.

[0096] The amount of silicon contained in the entire optical adjustment layer is preferably in the range of 5 mol % to 40 mol %, and more preferably in the range of 10 mol % to 33 mol %.

[0097] The thickness of the optical adjustment layer is preferably 10 nm to 100 nm. When the thickness of the optical adjustment layer is 10 nm or more, the surface of the glass substrate can be evenly covered, and when the thickness of the optical adjustment layer is 100 nm or less, new light interference in the optical adjustment layer can be suppressed, and the optical adjustment layer can exert the desired effect.

[0098] The thickness of the optical adjustment layer is more preferably 20 nm or more, further preferably 25 nm or more, particularly preferably 30 nm or more. In addition, the thickness of the optical adjustment layer is preferably 100 nm or less, more preferably 90 nm or less, further preferably 80 nm or less, particularly preferably 70 nm or less.

[0099] In addition, when the optical adjustment layer is composed of multiple layers of different materials, the “thickness” of the optical adjustment layer is represented by the total thickness of each layer.

[0100] In the present invention, the thickness of the film is preferably 500nm to 1600nm. When the thickness of the film is 500nm or more, the crystal grains in the film grow sufficiently, so that the emissivity can be improved, and the transmittance can be easily adjusted. In addition, when the thickness of the film is 1600nm or less, the thickness of the substrate with the film will not become too thick.

[0101] (Other layers)

[0102] The substrate with a film of the present invention may have other layers within a range not impairing the effects of the present invention.

[0103] As other layers, an overcoat layer and the like can be cited.

[0104] (Physical properties of the substrate with film)

[0105] The transmittance of the substrate with a film according to the present invention based on the standard A light source (Tva, A light source transmittance) is less than 30%. When the A light source transmittance (Tva) is less than 30%, sufficient heat ray absorption can be ensured.

[0106] The A light source transmittance (Tva) is preferably 28% or less, more preferably 25% or less, further preferably 20% or less, and particularly preferably 13% or less. In addition, from the viewpoint of obtaining an ideal appearance when used in automobiles and buildings, the A light source transmittance (Tva) is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, particularly preferably 4% or more, and most preferably 5% or more.

[0107] The light source A transmittance (Tva) can be measured using a commercially available spectrophotometer (for example, “Lambda 1050” manufactured by PerkinElmer).

[0108] In addition, the solar transmittance (Te) of the film-carrying substrate is preferably less than 30%. When the solar transmittance (Te) is less than 30%, sufficient heat ray absorptivity can be ensured.

[0109] The solar transmittance (Te) is more preferably 28% or less, further preferably 25% or less, and particularly preferably 20% or less. In addition, from the viewpoint of obtaining an ideal appearance when used in automobiles and buildings, the solar transmittance (Te) is preferably 1% or more, more preferably 2% or more, and further preferably 4% or more.

[0110] The solar energy transmittance (Te) can be measured using a commercially available spectrophotometer (for example, “Lambda 1050” manufactured by PerkinElmer).

[0111] It should be noted that by adjusting the impurity concentration in the film and the thickness of each layer constituting the film, the A light source transmittance and the solar energy transmittance can be adjusted to achieve the desired transmittance.

[0112] In addition, the emissivity (En) of the film-side surface of the substrate with a film is less than 0.25. When the emissivity (En) of the film-side surface is less than 0.25, excellent heat barrier properties can be obtained.

[0113] The emissivity (En) is more preferably 0.23 or less, further preferably 0.20 or less, and particularly preferably 0.17 or less. In addition, the lower the emissivity, the better the thermal barrier properties, so there is no particular restriction on the lower limit of the emissivity, but it is preferably 0.01 or more, more preferably 0.02 or more, and further preferably 0.04 or more.

[0114] Emissivity is the ratio of the energy of light emitted by an object due to thermal radiation (radiant brightness) to the energy of light emitted by a black body at the same temperature (black body radiation) set to 1. The emissivity of a substrate with a film can be measured by the method described in JIS R3106 (2019) using a commercially available emissometer (e.g., "Emissometer model AE1" manufactured by Devices & Services) on the film side surface.

[0115] The emissivity can be adjusted to a desired value by adjusting the film thickness, carrier density, mobility, sheet resistance, etc. of the infrared reflective layer.

[0116] In addition, the sheet resistance of the substrate with the film is preferably 30Ω / □ (ohm / square) or less. Emissivity is related to sheet resistance, and when the sheet resistance is 30Ω / □ or less, electricity flows easily, so the emissivity decreases, thereby achieving excellent thermal barrier properties.

[0117] The sheet resistance is more preferably 25Ω / □ or less, and further preferably 20Ω / □ or less. In addition, since the lower the sheet resistance, the easier it is for electricity to flow and the lower the emissivity, there is no particular restriction on the lower limit of the sheet resistance, but it is preferably 1Ω / □ or more, more preferably 2Ω / □ or more, and further preferably 3Ω / □ or more.

[0118] The value of the sheet resistance can be determined by Hall effect measurement.

[0119] When the substrate with a film of the present invention is incident with light from a D65 light source at an incident angle of 10 degrees, the reflected color L * a * b * Chromaticity coordinate a in the color system * Preferably -20 to 5, b * Preferably -20 to 10. * a * b * In the color system, a * and b * Indicates color and chroma, when a * Big(+a * ), indicating the red direction, when a * Small (-a * ), it indicates the green direction, and when b * Big(+b * ) indicates the yellow direction, when b * Small (-b * ) indicates the blue direction.

[0120] a *The value is more preferably -15 or more, and further preferably -12 or more. * The value is more preferably 2 or less, and even more preferably 0 or less. * The value is more preferably -15 or more, and further preferably -10 or more. * The value is more preferably 5 or less, and even more preferably 2 or less.

[0121] In addition, when the substrate with a film of the present invention is incident with light from a D65 light source at an incident angle of 10 degrees, the reflected color L * a * b * Chromaticity coordinate L in color system * 42 or less. * Indicates brightness, when L * When the value is 42 or less, the intensity of reflected light can be suppressed, and undesired images can be suppressed. * The value is more preferably 40 or less, and further preferably 35 or less. In addition, there is no particular restriction on the lower limit value, but when considering the reflectivity of a normal infrared reflection layer, L * The value is preferably 20 or more, more preferably 25 or more, and particularly preferably 30 or more.

[0122] a * Value, b * Value and L * The value can be measured by an ultraviolet visible spectrophotometer or a colorimeter, and the value when irradiated with light of a D65 light source at an incident angle of 10 degrees is measured using these measuring instruments.

[0123] In the present invention, by adjusting the impurity concentration in the film and the thickness of each layer constituting the film, a can be adjusted. * 、b * Value and L * values ​​so that they become the desired values.

[0124] In addition, the mobility of the membrane of the substrate with a membrane is preferably 20 cm 2 / Vs or more. The higher the mobility, the better the conductivity, and as a result, the better the thermal barrier. When the mobility is 20cm 2 / Vs or more, excellent heat barrier properties can be obtained.

[0125] The membrane mobility is more preferably 25 cm 2 / Vs or more, more preferably 27cm 2 / Vs or more, particularly preferably 30cm 2 / Vs or more, most preferably 35cm 2 / Vs or more. In addition, the higher the mobility, the better, so there is no particular upper limit, but it is preferably 100cm2 / Vs or less, more preferably 90cm 2 / Vs or less, more preferably 80cm 2 / Vs or less.

[0126] In addition, the substrate with a film preferably has an infrared reflective layer with a mobility of 20 cm 2 / Vs or more. When the mobility is 20cm 2 / Vs or more, excellent heat barrier properties can be obtained.

[0127] The mobility of the infrared reflection layer is more preferably 25 cm 2 / Vs or more, more preferably 27cm 2 / Vs or more, particularly preferably 30cm 2 / Vs or more, most preferably 35cm 2 / Vs or more. In addition, the higher the mobility, the better, so there is no particular upper limit, but it is preferably 100cm 2 / Vs or less, more preferably 90cm 2 / Vs or less, more preferably 80cm 2 / Vs or less.

[0128] In addition, the mobility of the substrate with a film and the infrared reflection layer can be measured by Hall effect measurement.

[0129] The carrier density of the substrate with the film is preferably 1×10 19 / cm 3 The carrier density refers to the number of free electrons or holes per unit volume in a substance. When the carrier density of the substrate with the film is 1×10 19 / cm 3 When the above values ​​are met, excellent heat barrier properties can be obtained.

[0130] The carrier density of the substrate with the film is more preferably 2×10 19 / cm 3 More preferably, 5×10 19 / cm 3 More than 1×10 20 / cm 3 In addition, the higher the carrier density, the better, so there is no particular upper limit, but it is preferably 1×10 22 / cm 3 Below, more preferably 1×10 21 / cm 3 Below, more preferably 5×10 20 / cm 3 the following.

[0131] In addition, it is preferred that the carrier density of the infrared reflection layer of the film-bearing substrate is 1×10 19 / cm 3 When the carrier density of the infrared reflection layer is 1×10 19 / cm 3 When the above values ​​are met, excellent heat barrier properties can be obtained.

[0132] The carrier density of the infrared reflection layer is more preferably 2×10 19 / cm 3 More preferably, 5×10 19 / cm 3 More than 1×10 20 / cm 3 In addition, the higher the carrier density, the better, so there is no particular upper limit, but it is preferably 1×10 22 / cm 3 Below, more preferably 1×10 21 / cm 3 Below, more preferably 5×10 20 / cm 3 the following.

[0133] In addition, the carrier density of the film-attached substrate and the infrared reflection layer can be measured by Hall effect measurement.

[0134] In addition, the haze of the film-attached substrate is preferably 10% or less. When the haze is 10% or less, visual recognition of white turbidity in the film-attached substrate can be suppressed, and a film-attached substrate having excellent aesthetics can be obtained.

[0135] The haze is more preferably 9% or less, further preferably 7% or less, and particularly preferably 5% or less. The smaller the haze, the better, so there is no particular lower limit.

[0136] The haze can be measured using a commercially available measuring instrument (for example, a haze meter "HZ-V3" manufactured by Suga Test Instruments Co., Ltd.).

[0137] (Method for producing a film-attached substrate)

[0138] Next, refer to Figure 3 , an example of the method for producing the film-attached substrate of the present invention is described.

[0139] It should be noted that, here, as an example, Figure 1 The manufacturing method will be described by taking the substrate 10 with a film shown as an example.

[0140] Figure 3 An example of a flow of a method for producing the film-attached substrate 10 is schematically shown.

[0141] like Figure 3 As shown, the method for producing a substrate with a film of the present invention has the following steps:

[0142] (a) a step of providing a heat ray absorbing layer on a first surface of a glass substrate (step S1); and

[0143] (b) A step of providing an infrared reflecting layer on the heat ray absorbing layer (step S2).

[0144] (Step S1)

[0145] First, a glass substrate is prepared. As described above, there is no particular limitation on the type of the glass substrate, and the glass substrate may be a soda-lime-silicate high-transmittance glass.

[0146] In step S1 , a heat ray absorbing layer is formed on a first surface of a glass substrate.

[0147] The heat ray absorbing layer can be formed by various film forming methods such as chemical vapor deposition (CVD), electron beam evaporation, vacuum evaporation, sputtering and spraying. Among them, in order to obtain excellent heat ray absorption, Sb needs to replace the Sn site and enter the crystal structure, and a high temperature process is required for this purpose, so it is preferably formed by a thermal CVD method. In addition, when it can be formed by an atmospheric pressure CVD method, a large vacuum device is not required, which can further improve productivity.

[0148] As described above, the heat ray absorbing layer is composed of various thin film materials such as tin oxide, indium oxide, zinc oxide, antimony-doped tin oxide (ATO), fluorine-doped tin oxide (FTO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO), and aluminum-doped zinc oxide (AZO).

[0149] For example, a case where an infrared reflection layer is formed of fluorine-doped tin oxide (FTO), a heat ray absorption layer is formed of antimony-doped tin oxide (ATO), and each layer is formed by a thermal CVD method will be described.

[0150] The heat ray absorbing layer uses a mixture of an inorganic or organic tin-containing compound and an antimony-containing compound as a raw material.

[0151] Examples of tin-containing compounds include monobutyltin trichloride (C 4 H 9 SnCl 3 ) and tin tetrachloride (SnCl 4) etc. As the tin-containing compound, an organic tin-containing compound is particularly preferred. When an inorganic tin-containing compound is used as the tin-containing compound, the growth rate of the crystal grains is fast and the surface irregularities tend to become serious.

[0152] Examples of antimony-containing compounds include antimony trichloride (SbCl 3 ) and antimony pentachloride (SbCl 5 ) etc. As the antimony-containing compound, antimony trichloride is particularly preferred. For example, antimony trichloride reacts violently with water in the raw gas to produce antimony trioxide (Sb 2 O 3 ) and antimony pentoxide (Sb 2 O 5 ) particle clusters. Therefore, by including these particle clusters in the film, the degree of surface roughness can be controlled.

[0153] In the film formation of the heat ray absorbing layer, the raw material gas may be transported after being mixed in advance. Alternatively, the raw material gas may be mixed on the surface of the glass substrate as the film formation object. In the case where the raw material is liquid, the raw material can be vaporized into a gas state using a bubbling method, a vaporization device, etc.

[0154] The amount of water is preferably set to 5 mol to 50 mol relative to 1 mol of the tin-containing compound in the raw material gas.

[0155] When the amount of water is less than 5 mol, the resistance value of the formed film tends to increase, and as a result, the heat ray absorption function caused by antimony tends to decrease. In addition, the starting point of nucleation decreases, and as a result, the grains tend to grow larger and the surface unevenness tends to become serious. On the other hand, when the amount of water is greater than 50 mol, as the amount of water increases, the raw gas capacity increases, the flow rate of the raw gas increases, and the film forming efficiency may decrease. In addition, the starting point of nucleation increases, and as a result, the grains tend to grow smaller and the surface tends to become flat.

[0156] In the case where the raw material gas contains oxygen, the amount of oxygen is preferably set to be greater than 0 mol and less than or equal to 40 mol, and more preferably set to 4 mol to 40 mol, relative to 1 mol of the tin-containing compound in the raw material gas. When the amount of oxygen is too small, the resistance value of the generated film sometimes increases, so the amount of oxygen is more preferably 4 mol or more. On the other hand, when the amount of oxygen is greater than 40 mol, the raw material gas capacity increases, the flow rate of the raw material gas increases, and thus the film forming efficiency may decrease.

[0157] The temperature of the glass substrate when forming the heat ray absorbing layer is preferably 500°C to 650°C.

[0158] When the temperature of the glass is less than 500°C, the formation speed of the heat ray absorbing layer sometimes decreases. In addition, the speed at which the precursor generated by the decomposition of the raw material gas diffuses on the surface of the glass and the heat ray absorbing layer is greater than the speed at which it reacts on the surface of the glass and the heat ray absorbing layer. As a result, more precursors flow into the unevenness on the surface of the glass and the heat ray absorbing layer, and the surface tends to become flat. On the other hand, when the temperature of the glass is greater than 650°C, film formation is carried out in a state where the viscosity of the glass is low, so warping may occur in the process of cooling the glass to room temperature. In addition, the speed at which the above-mentioned precursor reacts on the surface of the glass and the heat ray absorbing layer is greater than the speed at which the above-mentioned precursor diffuses on the surface of the glass and the heat ray absorbing layer. As a result, less precursors flow into the unevenness on the surface of the glass and the heat ray absorbing layer, and the unevenness on the surface tends to become larger.

[0159] (Step S2)

[0160] Next, an infrared reflecting layer is formed on the heat ray absorbing layer.

[0161] The infrared reflection layer can also be formed by various film forming methods such as chemical vapor deposition (CVD), electron beam evaporation, vacuum evaporation, sputtering and spraying, as with the heat ray absorption layer. Among them, in order to obtain excellent infrared reflectivity, F needs to replace the O site and enter the crystal structure, and a high temperature process is required for this purpose, so it is preferably formed by a thermal CVD method. In addition, when it can be formed by an atmospheric pressure CVD method, a large vacuum device is not required, which can further improve productivity.

[0162] As described above, the infrared reflection layer can be formed using various thin film materials such as fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO), and aluminum-doped zinc oxide (AZO).

[0163] When the infrared reflective layer is made of, for example, fluorine-doped tin oxide (FTO) or antimony-doped tin oxide (ATO), the surface irregularities of the infrared reflective layer can be increased, making it easier to adjust the color tone to a predetermined range.

[0164] When the infrared reflective layer is composed of, for example, aluminum-doped zinc oxide (AZO) or gallium-doped zinc oxide (GZO), the crystal orientation is easily aligned and the surface is easily flattened.

[0165] In addition, tin-doped indium oxide (ITO) has a strong infrared reflection function and is mostly used in a film thickness region of about 100 nm. Therefore, when the infrared reflection layer is composed of tin-doped indium oxide (ITO), it is sometimes difficult to adjust the hue of the reflected color to a specified range, the growth of the grains is insufficient, and the surface tends to become flat.

[0166] For example, when the infrared reflective layer is composed of a fluorine-doped tin oxide layer (FTO) and is formed by a thermal CVD method, a mixture of an inorganic or organic tin-containing compound and a fluorine-containing compound is used as a raw material.

[0167] As the tin-containing compound, monobutyltin trichloride (C 4 H 9 SnCl 3 ) and tin tetrachloride (SnCl 4 ) etc. As the tin-containing compound, an organic tin-containing compound is particularly preferred. When an inorganic tin-containing compound is used as the tin-containing compound, the growth rate of the crystal grains is fast and the surface irregularities tend to become serious.

[0168] Examples of the fluorine-containing compound include hydrogen fluoride and trifluoroacetic acid.

[0169] In the film formation of the infrared reflective layer, the raw material gas may be transported after being mixed in advance. Alternatively, the raw material gas may be mixed on the surface of the film-forming object (specifically, the heat ray absorbing layer). In the case where the raw material material is a liquid, the raw material material may be vaporized into a gaseous state using a bubbling method, a vaporization device, or the like.

[0170] The amount of water is preferably set to 5 mol to 50 mol relative to 1 mol of the tin-containing compound in the raw material gas.

[0171] When the amount of water is less than 5 mol, the resistance value of the formed film tends to increase, resulting in a decrease in infrared reflection function. In addition, the starting point of nucleation decreases, resulting in a large growth of crystal grains and a serious surface unevenness. On the other hand, when the amount of water is greater than 50 mol, as the amount of water increases, the raw gas capacity increases, the flow rate of the raw gas increases, and the film forming efficiency is likely to decrease. In addition, the starting point of nucleation increases, resulting in a small growth of crystal grains and a flat surface.

[0172] When the raw material gas contains oxygen, the amount of oxygen is preferably greater than 0 mol and less than or equal to 40 mol, and more preferably set to 4 mol to 40 mol, relative to 1 mol of the tin-containing compound in the raw material gas. When the amount of oxygen is less than 4 mol, the resistance value of the generated film sometimes increases. On the other hand, when the amount of oxygen is greater than 40 mol, the raw material gas capacity increases, the flow rate of the raw material gas increases, and the film forming efficiency may decrease.

[0173] In the film formation of the infrared reflective layer, the amount of the fluorine-containing compound is preferably set to 0.1 mol to 1.2 mol relative to 1 mol of the tin-containing compound in the raw material gas. When the amount of the fluorine-containing compound is less than 0.1 mol or when the amount of the fluorine-containing compound is greater than 1.2 mol, the resistance value of the formed film tends to increase.

[0174] The temperature when forming the infrared reflection layer is preferably 500°C to 650°C.

[0175] When the processing temperature is less than 500°C, the formation speed of the infrared reflective layer sometimes decreases. In addition, the speed at which the precursor generated by the decomposition of the raw material gas diffuses on the surface of the glass and the infrared reflective layer is greater than the speed at which it reacts on the surface of the glass and the infrared reflective layer. As a result, more precursors flow into the unevenness of the surface of the glass and the infrared reflective layer, and the surface tends to become flat. On the other hand, when the processing temperature is greater than 650°C, film formation is carried out in a state where the viscosity of the glass is low, so warping may occur in the process of cooling the glass to room temperature. In addition, the speed at which the above-mentioned precursor reacts on the surface of the glass and the infrared reflective layer is greater than the speed at which it diffuses on the surface of the glass and the infrared reflective layer. As a result, less precursors flow into the unevenness of the surface of the glass and the infrared reflective layer, and the unevenness of the surface tends to become larger.

[0176] It should be noted that step S1 and step S2 can be implemented by an online method in the process of manufacturing a glass substrate using a float glass process. Alternatively, the glass substrate manufactured by the float glass process can be reheated by an offline method to form a film. From the perspective of manufacturing efficiency, it is preferred to form a film by performing step S1 and step S2 by a thermal CVD method on a production line of a glass substrate.

[0177] (Other steps)

[0178] In the present invention, when an optical adjustment layer is provided between the glass substrate and the heat ray absorbing layer, the optical adjustment layer is disposed on the first surface of the glass substrate before step S1.

[0179] The optical adjustment layer can be formed by various film-forming methods such as chemical vapor deposition (CVD), electron beam evaporation, vacuum evaporation, sputtering, chemical plating, wet coating, and spraying, similarly to the heat ray absorbing layer and the infrared reflecting layer. Preferably, the method is the same as that of step S1 and step S2.

[0180] As described above, the optical adjustment layer can be made of, for example, SiOC, SiO 2 、TiO 2 SnO 2 And other film materials.

[0181] In addition, the optical adjustment layer may include a single layer, or may be a stack of two or more layers.

[0182] For example, when the optical adjustment layer includes a silicon oxycarbide (SiOC) layer, the optical adjustment layer can be formed by a thermal CVD method. In this case, as a raw material, for example, a silicon oxysilane (SiH 4), a mixed gas of ethylene and carbon dioxide. When such a carbon-containing gas is used, it is easy to form a particulate silicon compound together with a film-like silicon compound, which can increase the haze rate.

[0183] The raw material gases may be mixed in advance and delivered to the first surface of the glass substrate. Alternatively, the raw material gases may be mixed on the first surface of the glass substrate.

[0184] In addition, for example, the optical adjustment layer contains silicon oxide (SiO 2 ) layer, as a raw material, for example, monosilane (SiH 4 ), tetraethoxysilane and oxygen and other mixed gases.

[0185] In addition, for example, the optical adjustment layer contains titanium oxide (TiO 2 ) layer, as the raw material, for example, tetraisopropyl titanate (TTIP), titanium tetrachloride, etc. Among them, tetraisopropyl titanate (TTIP) is more preferred.

[0186] The temperature of the glass substrate when forming the optical adjustment layer is preferably 500° C. to 900° C. When the temperature of the glass substrate is lower than 500° C. or higher than 900° C., the film formation rate tends to decrease.

[0187] For example, in the case of forming a SiO x C y The layer (hereinafter also referred to as SiO x C y A method of using a layer) as an optical adjustment layer is described below.

[0188] In the CVD method, it is preferred that, for example, a glass substrate heated to a temperature of 500° C. to 800° C. is reacted with a gas raw material to form SiO on the glass substrate. x C y layer.

[0189] From the viewpoint of increasing the reaction rate of the CVD method, the temperature of the glass substrate is preferably 500° C. or higher, more preferably 600° C. or higher, and further preferably 700° C. or higher. From the viewpoint of glass softening, the temperature of the glass substrate is more preferably 800° C. or lower, and further preferably 760° C. or lower.

[0190] The gas feedstock preferably comprises a silicon-containing material, an oxidant and an unsaturated hydrocarbon.

[0191] Examples of silicon-containing substances include monosilane (SiH 4 ), disilane (Si 2 H 6 ), dichlorosilane (SiH 2 Cl 2), silane trioxide (SiHCl 3 ) and other silanes; tetramethylsilane ((CH 3 ) 4 Si) and other alkyl silanes; silicon tetrafluoride (SiF 4 ), silicon tetrachloride (SiCl 4 ) etc., preferably silanes, more preferably monosilane.

[0192] As the oxidizing agent, carbon dioxide (CO 2 ), carbon monoxide (CO), oxygen (O 2 ), water vapor (H 2 O) and other oxygen-containing compounds, preferably carbon dioxide.

[0193] Examples of the unsaturated hydrocarbons include ethylene-based unsaturated hydrocarbons (olefins), acetylene-based unsaturated hydrocarbons, aromatic compounds, and the like, and compounds that are gaseous at normal temperature and pressure are preferred.

[0194] The unsaturated hydrocarbon is preferably an olefin, more preferably an olefin having 2 to 4 carbon atoms, and further preferably ethylene.

[0195] By adjusting the mixing ratio of the gas raw materials, the SiO x C y SiO in the layer x C y composition.

[0196] Specifically, the volume ratio of the oxidant to the silicon-containing substance is preferably 8.5 or more, more preferably 12 or more, and even more preferably 20 or more. In addition, the volume ratio of the oxidant to the silicon-containing substance is preferably 50 or less.

[0197] The volume ratio of the unsaturated hydrocarbon to the silicon-containing substance is preferably 0.5 or more, more preferably 1.0 or more. In addition, the volume ratio of the unsaturated hydrocarbon to the silicon-containing substance is preferably 3.5 or less, more preferably 2.7 or less.

[0198] SiO x C y The composition of SiO changes due to the interaction between the above-mentioned oxidant and the unsaturated hydrocarbon. x C y The composition is adjusted to a preferred range. As for the volume ratio of the oxidant to the silicon-containing substance and the volume ratio of the unsaturated hydrocarbon to the silicon-containing substance, the combination of the two is important, and it is preferred that both be set to the above-mentioned preferred range.

[0199] From the perspective of sufficient coverage, SiO x C yThe thickness of the layer is preferably 10 nm or more, more preferably 20 nm or more, and further preferably 25 nm or more. x C y From the viewpoint of light absorption of the layer, the thickness is preferably 90 nm or less, more preferably 80 nm or less, and even more preferably 70 nm or less. x C y The thickness of the layer can be controlled by the type of raw material, raw material gas concentration, the blowing flow rate of the raw material gas to the glass ribbon or glass substrate, the substrate temperature, the residence time of the reaction gas from the coating beam structure, etc.

[0200] When an overcoat layer is provided in the present invention, the overcoat layer is disposed on the surface of the infrared reflective layer after step S2.

[0201] The overcoat layer is formed by, for example, a wet method.

[0202] In this case, first, a coating solution for an outer coat layer is prepared.

[0203] The coating solution comprises a precursor of the metal oxide, an organic solvent and water. In addition, particles and / or solid substances may be added to the coating solution. The composition of the particles may be the same as or different from that of the precursor of the metal oxide.

[0204] Next, the coating solution is applied onto the infrared reflective layer of the substrate with a film.

[0205] The coating method is not particularly limited, and a common method such as spin coating can be used.

[0206] Next, the substrate with the film coated with the coating solution is subjected to a heat treatment in the air.

[0207] The temperature of the heat treatment is, for example, in the range of 80° C. to 650° C. Moreover, the heating time is, for example, in the range of 5 minutes to 360 minutes.

[0208] The heat treatment can be performed using a common device such as a hot air circulation oven or an IR heating oven. Alternatively, an overcoat layer can be formed from the coating solution by UV curing treatment or microwave treatment.

[0209] Thereby, an overcoat layer can be formed on the infrared reflection layer.

[0210] It should be noted that the above-mentioned heating treatment does not necessarily have to be performed at this stage. That is, the coating solution may also be heated by a heating step performed at another stage.

[0211] Through such steps, the film-attached substrate of the present invention can be produced.

[0212] The method for producing a film-bearing substrate of the present invention may further include a step of air-cooling or chemically strengthening the glass substrate (strengthening step). The strengthening step may be performed in any order, for example, before step S1 or after producing the film-bearing substrate.

[0213] By carrying out the strengthening step, the strength of the glass substrate and the obtained substrate with a film can be improved.

[0214] Furthermore, after the film is disposed on the glass substrate, the obtained film-attached substrate may be subjected to bending processing.

[0215] Alternatively, laminated glass may be obtained by bonding the substrate with a film of the present invention, the intermediate film, and the outer glass plate in this order.

[0216] Furthermore, it is obvious to those skilled in the art that various modifications can be made.

[0217] According to the present invention, by adjusting the impurity concentration and film thickness, a substrate with a film having desired heat barrier properties and light transmission properties can be obtained. Therefore, when manufacturing various laminated glasses, the intermediate layer can be made common, thereby improving productivity and reducing costs.

[0218] The substrate with a film of the present invention can be used, for example, for vehicle window glass (front windshield, rear window glass, side window glass, roof glass, etc.), building window glass, etc. In particular, laminated glass having the substrate with a film of the present invention, an intermediate film, and an outer glass plate in this order is suitable for a panoramic roof.

[0219] As described above, this specification discloses the following aspects.

[0220] <1> A substrate with a film, the substrate with a film comprising a glass substrate and a film arranged on the glass substrate, wherein the glass substrate has a thickness of 5 mm or less, the glass substrate has a first surface and a second surface opposite to each other, the film is arranged on the first surface of the glass substrate, the transmittance of the substrate with the film based on a standard A light source is less than 30%, and the emissivity of the side surface of the film is less than 0.25.

[0221] <2> The substrate with a film according to <1> above, wherein the sheet resistance value of the substrate with a film is 30Ω / □ or less.

[0222] <3> The substrate with a film according to <1> above, wherein the carrier density of the film is 1×10 19 / cm 3 above.

[0223] <4> The substrate with a film according to any one of <1> to <3> above, wherein the mobility of the film is 20 cm 2 / Vs or above.

[0224] <5> The substrate with a film according to any one of <1> to <4> above, wherein the solar energy transmittance of the substrate with a film is less than 30%.

[0225] <6> The substrate with a film according to any one of <1> to <5> above, wherein the transmittance based on the standard A light source is 3% to 13%.

[0226] <7> The substrate with a film according to any one of <1> to <6> above, wherein the transmittance based on the standard A light source is 5% to 13%.

[0227] <8> The substrate with a film according to any one of <1> to <7>, wherein the film includes a heat ray absorbing layer and an infrared reflecting layer in this order from the glass substrate side.

[0228] <9> The substrate with a film as described in <8> above, wherein the infrared reflecting layer includes a film of at least one doped metal oxide selected from the group consisting of fluorine-doped tin oxide, antimony-doped tin oxide, tin-doped indium oxide, gallium-doped zinc oxide, and aluminum-doped zinc oxide.

[0229] <10> The substrate with a film according to <8> or <9>, wherein the infrared reflective layer comprises a fluorine-doped tin oxide film.

[0230] <11> The substrate with a film according to any one of <8> to <10>, wherein the infrared reflective layer has a thickness of 100 nm to 400 nm.

[0231] <12> The substrate with a film according to any one of <8> to <11>, wherein the heat ray absorbing layer includes a film of antimony-doped tin oxide.

[0232] <13> The substrate with a film according to <12> above, wherein the concentration of antimony contained in the heat ray absorbing layer is 5 mol % to 20 mol %.

[0233] <14> The substrate with a film according to any one of <8> to <13>, wherein the heat ray absorbing layer has a thickness of 300 nm to 700 nm.

[0234] <15> The substrate with a film according to any one of <8> to <14>, wherein the film further includes an optical adjustment layer, and the optical adjustment layer is disposed between the glass substrate and the heat ray absorbing layer.

[0235] <16> The substrate with a film according to <15> above, wherein the optical adjustment layer comprises a film selected from the group consisting of SiOC film, SiOC / SiO 2 Laminated film, TiO 2 / SiO 2 Laminated film and SnO 2 / SiO 2 At least one film of the group consisting of laminated films.

[0236] <17> The substrate with a film according to <15> above, wherein the optical adjustment layer includes a SiOC film.

[0237] <18> The substrate with a film according to any one of <1> to <15>, wherein the film is formed by a thermal CVD method.

[0238] <19> The substrate with a film according to <18>, wherein the film is formed by the thermal CVD method in a production line for the glass substrate.

[0239] <20> A vehicle window glass comprising the substrate with a film according to any one of <1> to <19>.

[0240] <21> A laminated glass comprising the substrate with a film according to any one of <1> to <19>, an intermediate film, and an outer glass plate in this order.

[0241] <22> The laminated glass according to <21>, wherein the laminated glass is used for a roof of a vehicle.

[0242] <23> A panoramic roof, comprising the laminated glass described in <21> above.

[0243] Example

[0244] The present invention is described in detail below by way of examples, but the present invention is not limited thereto. It should be noted that, regarding the following prepared examples, Examples 1 to 19 are examples, and Examples 20 to 23 are comparative examples.

[0245] (Measurement of thickness of each layer)

[0246] The substrate with the film was cut in the thickness direction, and the cross section was observed using a scanning electron microscope (SEM, "SU 70" manufactured by Hitachi, Ltd.).

[0247] In the case where the interface of the heat ray absorption layer and the infrared reflection layer can be confirmed by SEM observation, the film thickness of each layer is directly investigated from the SEM image. In the case of unevenness on the interface, the film thickness of each layer is derived while taking the middle line of each horizontal line of the lowest valley and the highest peak as the reference. When the observation magnification is too low, the accuracy of the film thickness measurement is insufficient. On the other hand, when the observation magnification is too high, local unevenness is seen, and it may not be possible to accurately derive the film thickness of each layer, so there is a suitable range. Therefore, as the standard of observation conditions, an electron gun of 1.5kV, a working distance of 2.4mm, and a magnification of 50,000 times are adopted.

[0248] When the interface between the heat ray absorbing layer and the infrared reflecting layer cannot be confirmed by SEM observation, the sum of the film thicknesses of the heat ray absorbing layer and the infrared reflecting layer is investigated from the SEM image, and then the film thickness ratio of the heat ray absorbing layer and the infrared reflecting layer is investigated by depth analysis using X-ray photoelectron spectroscopy (XPS). -6 In an XPS chamber of Pa, XPS measurement is performed while etching the film using Ar sputtering. The irradiation area of ​​X-rays is fixed at 100μmφ, and the irradiation angle of X-rays is fixed at 45 degrees. The heat ray absorption layer in this example is an ATO (antimony-doped tin oxide) film, so the midpoint between the point (time) at which the molar ratio of Sb obtained by depth analysis using XPS begins to increase relative to the etching time and the point (time) at which the slope of the increase is approximately zero is set as the interface between the heat ray absorption layer and the infrared reflection layer. In addition, the optical adjustment layer in this example is a SiOC film, so the intersection point where the molar ratios of Sn and Si show the same value is set as the interface between the heat ray absorption layer and the optical adjustment layer. According to this method, the film thickness of each layer can be derived with high reproducibility while referring to the etching rates of the heat ray absorption layer and the infrared reflection layer measured in advance using a single-layer film. In the derivation of the molar ratio of each atom, the software PHIMULTIPAC manufactured by ULVAC is used to calculate the composition based on the X-ray peak intensity. As XPS analysis conditions, the electron information of O1s, Si2p, Sn3d5, and Sb3d3 orbitals was referenced. However, since the peak positions of O1s and Sb3d5 overlap, in the derivation of the molar ratio of each atom, calibration was performed by subtracting 1.5 times the Sb3d3 peak intensity from the O1s peak intensity based on principle.

[0249] The XPS used the "PHI 5000Versa Probe" manufactured by ULVAC-PHI.

[0250] (Determination of Antimony (Sb) Concentration)

[0251] The antimony concentration was analyzed in the depth direction by X-ray photoelectron spectroscopy (XPS) and investigated based on the intensity ratio of Sb and Sn. The XPS used the "PHI 5000 Versa Probe" manufactured by ULVAC-PHI. The XPS analysis method was the same as that used to evaluate the thickness of each layer.

[0252] (L * 、a * 、b * Determination of

[0253] The chromaticity of the substrate with a film when light from a D65 light source was incident at an incident angle of 10 degrees was measured using a spectrophotometer (“CM-2500d” manufactured by Konica Minolta, Inc.).

[0254] (Determination of Sheet Resistance)

[0255] The substrate with the film was cut into 1 cm squares, and the sheet resistance value was measured using a Hall meter (manufactured by Nanometrics, "HL5500PC").

[0256] (Measurement of transmittance)

[0257] The transmittance based on the standard A illuminant (Tva, A illuminant transmittance) and the solar transmittance (Te) of the substrate with the film were measured based on the transmission spectrum measured using "Lambda 1050" manufactured by PerkinElmer. Te was calculated according to the definition of JIS R3106 (2019). Tva was calculated according to the definition of the standard A illuminant.

[0258] (Determination of emissivity)

[0259] The emissivity on the infrared reflecting layer side of the substrate with a film was measured using an "Emissometer model AE1" manufactured by Devices & Services by the method described in JIS R3106 (2019).

[0260] (Measurement of Haze)

[0261] The haze of the substrate with a film was measured using a haze meter "HZ-V3" manufactured by Suga Test Instruments Co., Ltd.

[0262] (Determination of mobility)

[0263] The film-carrying substrate was cut into 1 cm squares, and the mobility of the layers (heat ray absorbing layer and infrared reflecting layer) flowing in the film-carrying substrate was measured using a Hall meter ("HL5500PC" manufactured by Nanometrics) (Van der Pauw method).

[0264] (Determination of Carrier Density)

[0265] The film-bearing substrate was cut into 1 cm squares, and the thin layer carrier density (1 / cm2) of the layers (heat ray absorbing layer and infrared reflecting layer) where electricity flows in the film-bearing substrate was measured using a Hall meter ("HL5500PC" manufactured by Nanometrics). 2 ) (Van der Pauw method), and divided it by the sum of the film thicknesses of the heat ray absorbing layer and the infrared reflecting layer, thereby deriving the carrier density (1 / cm) of the portion of the substrate with the film where the current flows (heat ray absorbing layer and infrared reflecting layer). 3 ).

[0266] (Example 1)

[0267] The substrate with the film was produced by the following method.

[0268] First, a glass substrate (soda-lime silicate glass: manufactured by AGC Corporation) having a thickness of 2.1 mm was prepared.

[0269] Monosilane (SiH) was supplied as a gas raw material at 0.364 kg / hour from a coating beam located at the most upstream side of the glass ribbon at a temperature of 760°C. 4 ), ethylene was supplied at 0.25 kg / hour as a gas raw material, CO was supplied at 12.5 kg / hour as a gas raw material 2 The gas was supplied at 1.0 kg / hour as a nitrogen gas as a gas raw material, thereby forming a SiOC layer with a thickness of 70 nm on the glass ribbon.

[0270] Next, a heat ray absorbing layer was formed on the SiOC layer. The heat ray absorbing layer was antimony-doped tin oxide (SnO 2 :Sb, ATO), and the film was formed by thermal CVD method. Monobutyltin trichloride (C 4 H 9 SnCl 3 , MBTC), antimony trichloride (SbCl 3 ), water, air, and hydrogen chloride were used as raw material gases, and nitrogen was used as carrier gas. The target thickness of the heat ray absorbing layer was 500 nm.

[0271] Next, an infrared reflection layer is formed on the heat ray absorption layer. The infrared reflection layer is a fluorine-doped tin oxide layer (SnO 2 :F, FTO), film formation was performed by thermal CVD. Monobutyltin trichloride (C 4 H 9 SnCl 3, MBTC), water, air, trifluoroacetic acid (TFA), and nitric acid were used as raw material gases, and nitrogen was used as a carrier gas. The target thickness of the infrared reflective layer was 300 nm.

[0272] Thus, a substrate with a film was obtained.

[0273] (Examples 2~23)

[0274] A substrate with a film having the layer structure shown in Table 1 was prepared in the same manner as in Example 1. The antimony concentration was adjusted by adjusting the concentration of monobutyltin trichloride (MBTC) and antimony trichloride (SbCl 3 ) ratio to adjust.

[0275] The above-mentioned measurements were performed on each example. The results are shown in Table 1.

[0276]

[0277] From the results in Table 1, it can be seen that Examples 1 to 19 have low emissivity, excellent heat resistance, and low transmittance. This shows that both heat shielding performance and light shielding performance can be achieved.

[0278] Although the present invention is described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the subject matter and scope of the present invention. This application is based on Japanese patent applications (Japanese patent applications 2021-091745) filed on May 31, 2021 and Japanese patent applications (Japanese patent applications 2021-214754 and Japanese patent applications 2021-214755) filed on December 28, 2021, the contents of which are incorporated herein by reference.

[0279] Description of symbols

[0280] 1 Glass substrate

[0281] 1a Side 1

[0282] 1b Side 2

[0283] 2 Membrane

[0284] 3 Heat ray absorption layer

[0285] 5 Infrared reflection layer

[0286] 7 Optical adjustment layer

[0287] 10, 20 Substrate with film

Claims

1. A substrate with a laminated film, the substrate with a laminated film comprising a glass substrate and a laminated film arranged on the glass substrate, wherein: The visible light transmittance of the glass substrate based on standard A light source is 84.6% or more, the thickness of the glass substrate is 5 mm or less, the glass substrate has a first surface and a second surface opposite to each other, the laminated film is provided on the first surface of the glass substrate, and the laminated film includes a heat ray absorbing layer and an infrared reflecting layer in order from the glass substrate side, The heat ray absorbing layer includes a film of antimony-doped tin oxide, The visible light transmittance of the substrate with the laminated film based on the standard A light source is 25% or less, the solar energy transmittance of the substrate with the laminated film is 28% or less, and the emissivity of the laminated film side surface is less than 0.

25.

2. The substrate with a laminated film according to claim 1, wherein The sheet resistance value of the substrate with the laminated film is 30Ω / □ or less.

3. The substrate with a laminated film according to claim 1 or 2, wherein The carrier density of the stacked film is 1×10 19 / cm 3 above.

4. The substrate with a laminated film according to any one of claims 1 to 3, wherein The mobility of the laminated film is 20 cm 2 / Vs or above.

5. The substrate with a laminated film according to any one of claims 1 to 4, wherein The infrared reflection layer includes a film of at least one doped metal oxide selected from the group consisting of fluorine-doped tin oxide, antimony-doped tin oxide, tin-doped indium oxide, gallium-doped zinc oxide, and aluminum-doped zinc oxide.

6. The substrate with a laminated film according to any one of claims 1 to 4, wherein The infrared reflection layer includes a fluorine-doped tin oxide film.

7. The substrate with a laminated film according to any one of claims 1 to 6, wherein The infrared reflection layer has a thickness of 100 nm to 400 nm.

8. The substrate with a laminated film according to any one of claims 1 to 7, wherein The concentration of antimony contained in the heat ray absorbing layer is 5 mol % to 20 mol %.

9. The substrate with a laminated film according to any one of claims 1 to 8, wherein The thickness of the heat ray absorbing layer is 300 nm to 700 nm.

10. The substrate with a laminated film according to any one of claims 1 to 9, wherein The laminated film further includes an optical adjustment layer disposed between the glass substrate and the heat ray absorbing layer.

11. The substrate with a laminated film according to claim 10, wherein The optical adjustment layer has at least one film selected from the group consisting of a SiOC film, a SiOC / SiO 2 stacked film, a TiO 2 / SiO 2 stacked film, and a SnO 2 / SiO 2 stacked film.

12. The substrate with a laminated film according to claim 10, wherein The optical adjustment layer has a SiOC film.

13. The substrate with a laminated film according to any one of claims 1 to 12, wherein The total thickness of the heat ray absorbing layer and the infrared reflecting layer is 500 nm to 1500 nm.

14. The substrate with a laminated film according to any one of claims 1 to 13, wherein The emissivity is less than 0.

15.

15. A method for producing a substrate with a laminated film, which is the method for producing a substrate with a laminated film according to any one of claims 1 to 14, wherein: The stacked film is formed by a thermal CVD method.

16. The method for producing a substrate with a laminated film according to claim 15, wherein: The laminated film is formed by the thermal CVD method in a production line for the glass substrate.

17. A vehicle window glass, wherein: The vehicle window glass comprises the substrate with a laminated film according to any one of claims 1 to 14.

18. A laminated glass, wherein: The laminated glass comprises the substrate with a laminated film according to any one of claims 1 to 14, an intermediate film, and an outer glass plate in this order.

19. The laminated glass according to claim 18, wherein: The laminated glass is used for a roof of a vehicle.

20. A panoramic roof, wherein: The panoramic roof comprises the laminated glass according to claim 18 .

Citation Information

Patent Citations

  • Low radiation glass and glass article using the low radiation glass

    JP2001199744A

  • Glass products with solar control coatings

    JP2003535004A

  • Sunshine screen for vehicle window and vehicle window

    JP2008044609A

  • Method for producing carbon fiber composite material, and carbon fiber composite material

    JP2021091745A

  • Laminated panoramic roof with improved aesthetics

    WO2019008471A1